Resistência de genótipos de trigo à brusone - Arendt, Pablo Fernando (2006)
Wheat is a crop of great economical importance for the center-south area of Brazil with a cultivated area of approximately 2.359.000 ha which produced 4.721.500 tons in 2005. The wheat blast incited by the fungus Pyricularia grisea (Magnaporthe grisea), causes high yield losses to the wheat crop in some areas of Paraná, São Paulo, Mato Grosso do Sul and Goiás, reducing up to 50% of the production, in some farms. Chemical control of the disease is not yet satisfactory and there is not enough information on resistance. The main objective of this work was the evaluation of wheat genotypes for resistance to wheat blast, and to establish methodology for tests. Isolates of Pyricularia grisea used were collected in different wheat producing areas from the states of Goias, Paraná and São Paulo. Tests were done to determine the damp period and the appropriate temperature for the infection of wheat grown under controlled environment. It was also tested the inoculum concentration for inoculations. After the accomplishment of the test, it was possible to verify that selected isolates were virulent to all tested genotypes and that the severity of the disease varied according to the temperature and damp period that the plants were submitted. In all inoculum concentrations of the pathogen tested, there was development of the disease with a gradual increase according to the increase concentration of the inoculum. It was possible to make satisfactory evaluation of wheat genotypes for resistance to wheat blast in temperatures of 24th C and dump period of 24 hours. The evaluations of genotypes for resistance to wheat blast were carried out in greenhouse with controlled atmosphere. The selected genotypes were component of income trial and from the national collection of wheat Germoplasma Bank of Embrapa Trigo (BAG). The genotypes were grown in plastic pots, inoculated in a mist chamber at the heading stage and the evaluations of severity of head infection were accomplished 10 days after. The statistical Fastcluster of the SAS statistical package was used. One hundred and fifty genotypes were evaluated in three tests and the wheat varieties BR 18 and BRS 209 were used as moderately resistant and susceptible control, respectively. In the first experiment, the genotypes IPF 758669, LD 0324, BRS 120, BRS 220, BRS 49, LD 2010, PF 980503, PF 970177, PF 953239, PF 990692, IAPAR 53, IPF 75876, PF 999245, PF 980571, LD 0221, LD 0320, LD 2004, IA 0310 showed severity of the disease lower than 24,8% corresponding to control BR 18. In the second experiment the genotypes LD 0318, IA 0310, IA 0209, IPF 75869, LD 0320, PF 990695, PF 001104, LD 2007, LD 2004, PF 001102, BRS ANGICO, BRS BURITI and LD 0324 also shoved lower disease severity than BR 18 (35,6%). However, in the third experiment only the varieties PF 020042, LD 2004, PF 020043, PF 020051, PF 023201B, PF 020057 showed lower disease severity than control. The varieties that stood out as moderately resistant in the too experiments, besides the control BR 18, were LD 2004, LD 0320, LD 0324, PF 001102, IPF 75869, IA 0209, IA 0310 showing the best level of resistance reaction on the heads in both experiments. Some variations in results were observed for genotypes which migrated among the groups (MR, MS, S), however the difference in severity in most of these genotypes was not much accentuated